Assessing the risk of in-flight hypoxia: chronic lung disease of prematurity and children with neuromuscular disorders. Issue 4 (April 2015) - Hall, Graham L.; Withers, Adelaide
Abstract: Most children will experience a small, clinically insignificant drop in oxygen saturation during air travel due to the effects of altitude. Clinically significant hypoxia may occur in individuals with an underlying cardio-respiratory condition, in particular young infants born prematurely or with chronic lung disease of prematurity and in children with neuromuscular disorders. To date there is very little in-flight data available in these clinical populations to allow the development of evidence based guidelines for pre-flight assessment of the risk of hypoxia in-flight. The hypoxia flight simulation test is considered the gold standard for assessing the risk of in-flight hypoxia in adults and existing clinical guidelines for pre-flight assessment are largely based on data extrapolated from adults. The hypoxia challenge test has not been validated in infants and children and there are data to suggest that the test may not be accurate in neonates. We recommend high risk paediatric patients are assessed on a case by case basis by a respiratory paediatrician, with consideration of a hypoxia flight simulation test in certain circumstances.